Business process re-engineering: the technique to improve delivering speed of service industry in Tanzania - Sungau, Joseph Joseph; Ndunguru, Philibert C.; Kimeme, Joseph (Independent Journal of management & production, 2024)
This article published by the Independent Journal of management & production Vol. 4 No. 1 (2013):